IMPLEMENTASI BAHAN AJAR PENDIDIKAN ILMU PENGETAHUAN SOSIAL BERBASIS KEARIFAN LOKAL DI KELAS IV SEKOLAH DASAR NEGERI 04 BUANTAN BESAR KECAMATAN SIAK KABUPATEN SIAK - Eddy Noviana; Rifka Mahira Bakri (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2015)
This study aims to determine the effect of the implementation of teaching materials based Social Science Education Local Wisdom in class IV SDN 04 Buantan Besar Kecamatan Siak, which uses qualitative and quantitative approach with quasi-experimental methods (quasi-experiment), and by using the research form one group pretest-posttest design comparing scores between pretest and posttest scores. This study was conducted with three stages, namely (1) the preliminary stage; (2) the implementation phase; and (3) the final stage. Data collection techniques used in the study are interview techniques and testing techniques. The results showed that (1) implementation of teaching materials based on local wisdom PIPS effect on comprehension and learning outcome fourth grade students of SDN 04 Buantan Besar Kecamatan Siak with the large influence of 29.16%; (2) The implementation of teaching materials based PIPS Local Wisdom assist students in understanding the potential and conditions surrounding area, this is evidenced by the increase student’s understanding in study teaching materials of PIPS based on local wisdom, from the average pretest score of 30.22 into 55.43 on the average posttest scores with a mean score increase of 0.36 which is in the medium category.Keywords: implementation, instructional materials, local wisdom